The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s13613-017-0303-4
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of virtual-reality-based early neurocognitive stimulation in critically ill patients

Abstract: BackgroundGrowing evidence suggests that critical illness often results in significant long-term neurocognitive impairments in one-third of survivors. Although these neurocognitive impairments are long-lasting and devastating for survivors, rehabilitation rarely occurs during or after critical illness. Our aim is to describe an early neurocognitive stimulation intervention based on virtual reality for patients who are critically ill and to present the results of a proof-of-concept study testing the feasibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…47,48 Cognitive impairment in ICU patients deserves increased recognition and action from both clinicians and researchers. [48][49][50] In a 6-month observational study, Schmidt et al 51 assessed the prevalence of dyspnea in mechanically ventilated subjects in which 96 subjects were enrolled as soon as they could answer symptom-related questions assessing dyspnea caused by air hunger or respiratory effort, pain, and anxiety on visual analog scales. Interestingly, half of the subjects reported dyspnea, and dyspnea was associated with anxiety, assist/control ventilation, and increased heart rate.…”
Section: Asynchronies and Respiratory Sensationsmentioning
confidence: 99%
“…47,48 Cognitive impairment in ICU patients deserves increased recognition and action from both clinicians and researchers. [48][49][50] In a 6-month observational study, Schmidt et al 51 assessed the prevalence of dyspnea in mechanically ventilated subjects in which 96 subjects were enrolled as soon as they could answer symptom-related questions assessing dyspnea caused by air hunger or respiratory effort, pain, and anxiety on visual analog scales. Interestingly, half of the subjects reported dyspnea, and dyspnea was associated with anxiety, assist/control ventilation, and increased heart rate.…”
Section: Asynchronies and Respiratory Sensationsmentioning
confidence: 99%
“…The state-of-the-art therapy provided to critically ill patients focuses on physical rehabilitation, and there is currently no consensus on how to prevent cognitive impairments after ICU discharge (15,16). However, Turon et al showed that training of cognitive functions presented on a television screen is feasible and may be beneficial for critically ill patients (17).…”
Section: Introductionmentioning
confidence: 99%
“…In a prospective, longitudinal study conducted in 315 patients being weaned from prolonged ventilation at a long-term acute-care hospital [15] 84.7% of survivors indicated willingness to undergo mechanical ventilation again. Clinical investigations of the effects of various interventions, including new technologies (e.g., early neurocognitive rehabilitation software [16]) are urgently required to improve long-term outcome after critical illness.…”
Section: Mechanical Ventilation Longer Length Of Icu-staymentioning
confidence: 99%